Mortality and morbidity of stairlift injuries: Analysis of the UK TARN database. Issue 6 (June 2020) - O'Malley, O.; Ryan, O.; Wilson, G.; Islam, M.; Smith, T.O.; Hing, C.B.
Highlights: 16% of falls from a stairlift result in mortality. Mortality is associated with injuries to the thorax in those aged 70 years or below, injuries to the face, spine and limb for those aged 71–85 years and with head injury in those over 85 years. The most common injury from a stairlift is a limb injury whilst the most severe injuries are head injuries. Higher injury severity is associated with injuries from falling getting off astairlift. Abstract: Aims: To investigate the incidence and pattern of injury in patients with a diagnosis of a fall from a stairlift. Methods: Data was analysed from the Trauma Audit and Research Network (TARN) database from 2000 to 2018 for those recorded suffering stairlift related injuries between the ages of 40–100 years. Patient demographics, injury mechanism and pattern, mortality rate and height of fall were analysed. Results: 1069 patients were identified in the initial search with 651 having an eligible mechanism of injury. The mean age was 82 (range 41.4–100.1) years. The most common site of injury was the limbs (49.2%) with the most severe injuries to the head (mean AIS 3.1). The mean ISS was 12.5 (Range 1–75). There was no relationship between height of fall and ISS (rs 0.054 p = 0.4). Individuals were 78% more likely to have an ISS score of 15 or more if they had a head injury, (OR: 0.12; 95% CI: 0.06–0.24) and 79% more likely to have sustained an injury to the thorax (OR: 0.21; 95% CI: 0.11–0.41). Injury to the head was 95% more likely in individuals with an ISS score greater than 25 points or more (OR: 0.05; 95% CI: 0.01–0.16) and 69% more likely for those who sustain injury to the thorax. Individuals with an ISS score of 25 points or more were 18 times more likely to have sustained injury getting off their stair lift compared to any other method of falling from their stair lift. Mortality was associated with injuries to the thorax in those aged 70 years or below, injuries to the face, spine and limb for those aged 71–85 years and with head injury in those over 85 years. The overall mortality rate was 15.7%. Conclusion: Falls from stairlifts commonly result in limb injuries and most severe injuries are sustained to the head. When patients fall getting off from astairlift, have injuries to their head or thorax they have a higher ISS. The overall mortality is 15.7%. Given the increasing use of stairlifts in our ageing population, strategies should be considered to make these safer.